KAJIAN PSIKOANALISIS DALAM NOVEL BU, TIDAK ADA TEMAN MENANGIS MALAM INI KARYA BOY CANDRA - Septiany, Dinny; Priyadi, Antonius Totok; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to describe the results of Psychoanalytic Study in the Novel Bu There Are No Friends Tonight by Boy Candra. The research method used is a descriptive method in the form of qualitative research. The data source for this research is the Novel Bu, There Are No Friends Crying Tonight by Boy Candra and the data is the personality of the main character which is related to the id, ego, superego in the form of words, phrases, sentences that lead to the object of analysis. Data collection techniques use documentary study techniques. Data validity testing techniques are carried out using diligent observation, reference adequacy, and triangulation. The results of the research show the personality of the main character from the id aspect, including attention, romance, feelings of longing, eating with his wife and being surprised. The main character's personality from the ego aspect, includes trying, looking for busyness, calming down, controlling emotions and accepting reality. The main character's personality from the super-ego aspect, including saying goodbye, greeting and saying hello. Researchers have designed a module that utilizes the novel Bu, There Are No Friends Crying Tonight by Boy Candra as learning material in schools, specifically to achieve learning objectives 12.4 in class XII SMA.